2003
DOI: 10.1086/375376
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Chloroplast Dehydrin in Leaves of Mature Plants

Abstract: Several types of proteins are known to accumulate as a result of dehydration stress in plants, and many of these are thought to serve a protective function. This includes the dehydrin family of proteins, which accumulate in cells in response to drought, low temperatures, or salinity and in embryo tissues during the maturation phase of seed development, when the seed is losing water in preparation for dormancy. Many studies to date have concentrated on the expression, localization, and function of dehydrins in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Previous studies found that DHNs can be localized in the nucleus, chloroplasts, vacuole, rough endoplasmic reticulum, mitochondria, cytoplasm and membranes (Heyen et al. , 2002; Mueller et al. , 2003; Carjuzaa et al.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies found that DHNs can be localized in the nucleus, chloroplasts, vacuole, rough endoplasmic reticulum, mitochondria, cytoplasm and membranes (Heyen et al. , 2002; Mueller et al. , 2003; Carjuzaa et al.…”
Section: Resultsmentioning
confidence: 99%
“…Some dehydrins also accumulated in the vicinity of plasma membrane and were suggested to inhibit lipid peroxidation caused by ROS (Danyluk et al 1998). In the last a few years, dehydrins have been proved to be distributed in mitochondria and chloroplast (Borovskii et al 2000;Mueller et al 2003), which are known to be important ROS-generating places and susceptible to the attack of free radicals (Salin 1991). These results argued that the function of dehydrins is associated with ROS or dehydrins may play an antioxidative role in plants under environmental stresses.…”
Section: Many Studies Indicated That Plant Dehydrins Have Antioxidatimentioning
confidence: 98%
“…Some dehydrins can also be expressed constitutively during normal growth (Rodriguez et al 2005;Rorat et al 2004Rorat et al , 2006. Under stress conditions, DHNs accumulate in most tissues and cells and are mainly localized to the cytoplasm and nucleus of the plant cell (Close 1997;Mehta et al 2009;Rorat 2006;Tunnacliffe and Wise 2007), although some DHNs have been found to interact with the chloroplasts (Mueller et al 2003), mitochondria (Borovskii et al 2002), plasma membrane (Danyluk et al 1998;Puhakainen et al 2004), and tonoplasts (Heyen et al 2002;Saavedra et al 2006). Such a wide distribution and expression pattern suggests that these proteins play essential roles in plant growth and stress tolerance.…”
Section: Introductionmentioning
confidence: 99%